Environmental Assessment of Fishpond Water: Physicochemical and Microbial Analysis of Water Quality in Aquaculture - Vicencio, Pamila Erica L.; Dela Cruz, Missy Meine C.; Reyes, Angelica P. (Three E Science Institute, 2025)
This study assesses the water quality of selected fishponds in Barangay Binakod, Bulacan, Philippines, focusing on critical physicochemical and microbiological parameters necessary for sustainable aquaculture. Key parameters, including pH, temperature, turbidity, dissolved oxygen, phosphate, nitrate, fecal coliform, and total coliform, were measured through on-site field monitoring using calibrated water quality meters and laboratory analysis of water samples. To complement the quantitative data, interviews with fishpond owners were conducted to gather qualitative insights into feeding practices, fertilizer application, and other management practices that influence nutrient loads and water quality. The collected data were compared with the standard aquaculture water quality guidelines outlined in the Department of Environment and Natural Resources (DENR) Administrative Order No. 2016-008 for Class C water bodies. This comparison highlights deviations from the recommended standards and identifies factors contributing to potential water quality issues. The study also examines how these parameters impact the growth, survival, and overall health of aquatic organisms in the fishponds, providing a comprehensive understanding of the current water quality status. The findings of the study offer evidence-based recommendations to fishpond owners, focusing on improving water quality and enhancing aquaculture production. These recommendations address nutrient imbalances, optimize management practices, and reduce environmental impacts. The results of this research contribute to the sustainable management of aquaculture in Barangay Binakod and serve as a valuable reference for improving water quality and productivity in similar aquaculture systems. The importance of maintaining optimal water quality to ensure the long-term viability and profitability of aquaculture operations while promoting environmental sustainability.